Three level code division multiplexing in radio over fiber system - Doa'a Alzaqebah, Ali Ahmad (2022)
Recently, broadband internet users and the demands for communications with high data rates and wide coverage networks have grown exponentially all over the world. Radio over fiber (RoF) system has been introduced to compete with the demands. It is basically a combination of radio waves and optical fiber links that facilitates wireless access in a range of applications such as Wi-Fi (IEEE 802.11), which is one of the Wireless Local Area Network (WLAN) standards. RoF technology can provide a solution for Wi-Fi that is suffering from relatively low data rates and high loss as the main advantages of this technology are large bandwidth, low attenuation losses, and low power consumption. Despite the benefits of this technology, it is suffering from low quality of signals due to the noise and limited number of users, as each user must be assigned a special carrier frequency. The signal impairments in RoF system, such as noise and distortion, tend to limit the dynamic range of RoF links. Therefore, Three Level Division Multiplexing (3LCDM) technique is chosen to be implemented over RoF system since it is one of the best multiplexing techniques that allows two users to share the same channel which double the capacity. Code division in the 3LCDM technique is achieved by compiling two data streams within the multiple levels instead of the wavelength bandwidth, and this doubles the bandwidth efficiency. In this study, the 3LCDM over RoF system is proposed in WLAN IEEE802.11 (Wi-Fi) to enhance the performance in terms of number of users and receiver sensitivity. OptiSystem software in cooperation with MATLAB was used for the simulation, which is only for the downlink transmission. In this study, the performance of the 3LCDM over RoF system was investigated with 2.4 GHz, 5 GHz, and the combination of 2.4 GHz and 5 GHz carrier frequencies. The results show that the system with the combination of 2.4 GHz and 5 GHz carrier frequencies can support 4 users at a maximum data rate of 2x 0.5 Gbps and 43 km fiber length without any amplifier. It was also found that the power penalty for this particular proposed model over the maximum distance was 0.8 dB for the best user and less than 3 dB for the worst user. The system also displayed better performance than the conventional RoF by around 8.65 dB. In this study, the performance of the combination of 3LCDM over RoF over WDM for 8 users was also evaluated. By using the post-Dispersion Compensation Fiber (DCF), it was observed that the system at 2 x 0.5 Gbps for each carrier can achieve maximum distance of 57 km without using amplifiers. In addition, the performance of the worst user in 3LCDM-RoF-WDM system is better than that of the [50] in RoF over WDM system in terms of receiver sensitivity by around 7.94 dB. These findings prove the efficiency of the proposed 3LCDM-RoF and 3LCDM-RoFWDM systems to be applied in Wi-Fi.